Epilepsy and Child History in Dr. Jamal Ahmad Rashid Pediatric Teaching Hospital Sulaymaniyah /Iraq - Abdulkareem, Awayi Ghazy (Kurdistan Journal of Applied Research, 2022)
Epilepsy is a chronic neurological illness that is the most prevalent severe brain problem worldwide .The purpose of this research is to determine the importance of certain risk variables for epilepsy in children in Sulaimani City, such as age, gender, head trauma, nervous system infectious diseases including meningitis and unusual perinatal history, low birth weight, neonate respiratory failure, neonatal seizure, socioeconomic status, as well as parent consanguinity. This research was created based on 104 cases (where 51 of the patients were male, while 53 of the patients were female) among the inpatient and outpatient neurology unit of Dr. Jamal Ahmad Rashid Pediatric teaching Hospital from 20/12/2020 to 29/4/2021 . In this research, all the children were evaluated, as well as their medical & personal information were collected .A relation between the phenomenon of epilepsy with numerous risk factors were made; the ratio was calculated to determine the essential variables linked with epilepsy. Data was collected through interviewing of the patients then analyzed through the application statistical analysis descriptive. Results: age, head trauma, gender, febrile, positive family history for epilepsy, unusual perinatal history, and neonatal infection has been shown to have a statistically significant link to epilepsy. Conclusion: The majority of the samples was aged between six to ten while most of them were the middle child of their families. The results of survey also showed that most of the children were diagnosed between ages one to five while most of the samples have a generalized seizure. On the other hand, there was a statistical significant association between febrile convulsion and family history of epilepsy depending. Recommendation: Health staff (maternity staff) should not be excessively forced to pull the child’s delivery. Informing the child’s parents about the disease so that they do not become worried about any neurological disorders, our recommendation for staff working neurology field neurologist when such child enter the hospital immediately and quickly and get the necessary treatment.